Platelet Function Testing and Genotyping for Tailoring Treatment in Complex PCI Patients - Athanasios Moulias; Angeliki Papageorgiou; Dimitrios Alexopoulos (US Cardiology Review)
Dual antiplatelet therapy (DAPT), comprising aspirin and a P2Y12 receptor inhibitor, is considered the cornerstone of treatment in patients who have undergone percutaneous coronary intervention (PCI). Patients with complex PCI (C-PCI) constitute a special PCI subpopulation, characterized by increased ischemic risk. Identifying the optimal DAPT strategy is often challenging and remains controversial in this setting. In an attempt to balance ischemic and bleeding risks in C-PCI patients receiving DAPT, treatment individualization regarding potency and duration has evolved as a feasible approach. Platelet function testing and genotyping have been evaluated in several trials with conflicting and mostly neutral results. The aim of this review is to critically appreciate the role of these tools for antiplatelet treatment tailoring specifically in C-PCI patients. Because existing evidence is limited, dedicated future studies are warranted to elucidate the utility of platelet function testing and genotyping in C-PCI.